Energy Properties of Sunflower Seed Husk as Industrial Extrusion Residue (Agricultural Engineering, 2017)
The paper presents possibilities of using by ‒ products of the agri-food sector, in the form of sunflower husks, for energy purposes. Physical and chemical properties in the form of heat of combustion, calorific value for three moisture levels and ash content for two temperatures of combustion were determined and the carbon content (C), hydrogen content (H) and nitrogen content (N) were calculated pursuant to the PN-EN 15104 standard. Analysis of the heat of combustion and calorific value proved good energy properties of the investigated biomass. For the moisture level of 9%, 16%, 32% the heat of combustion was respectively 19.44 MJ∙kg-1, 17.94 MJ∙kg-1, 15.03 MJ∙kg-1, and the calorific value 18.09 MJ∙kg-1, 16.28 MJ∙kg-1, 13.16 MJ∙kg-1. The average ash content of the investigated biomass for the combustion temperature of 600°C and 815°C was respectively 2.12% and 2.04. In the analyzed biomass the nitrogen content was determined at the level of 1.57%, carbon of 43.87% and hydrogen of 6.29%.